2019
DOI: 10.1088/1361-6560/ab58fe
|View full text |Cite
|
Sign up to set email alerts
|

Primary, scatter, and penetration characterizations of parallel-hole and pinhole collimators for I-123 SPECT

Abstract: Multi-pinhole (MPH) collimators are known to provide better trade-off between sensitivity and resolution for preclinical, as well as for smaller regions in clinical SPECT imaging compared to conventional collimators. In addition to this geometric advantage, MPH plates typically offer better stopping power for penetration than the conventional collimators, which is especially relevant for I-123 imaging. The I-123 emits a series of high-energy (>300 keV, ~2.5% abundance) gamma photons in addition to the primary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 36 publications
0
17
0
Order By: Relevance
“…Many of these high-energy photons are assumed to pass through the crystals of the SPECT camera and undergo Compton scattering from the components adjacent to the crystals (e.g., photo-multiplier tubes and associated electronics). These inelastically scattered photons are then detected by re-entering the crystal with a lower energy contaminating the projection data recorded within the photopeak windows [ 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…Many of these high-energy photons are assumed to pass through the crystals of the SPECT camera and undergo Compton scattering from the components adjacent to the crystals (e.g., photo-multiplier tubes and associated electronics). These inelastically scattered photons are then detected by re-entering the crystal with a lower energy contaminating the projection data recorded within the photopeak windows [ 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…This is particularly an issue for the case of down-scatter from higher-energy photons, as for those emitted by 123 I with ~2-3% abundance in addition to its primary photon. Könik et al demonstrated that for 123 I DaTscan imaging, total scatter, multiple scatters, and penetration events for the low energy high resolution (LEHR) parallel-hole collimators were 2.5, 7.6 and 14 times more than that of an MPH collimator within the 15% photopeak window and with a 2-cm thick tungsten aperture plate (37).…”
Section: Review Articlementioning
confidence: 99%
“…Mok et al (37) found that the MPH SPECT for small FOV imaging is able to achieve high detection efficiency without much deterioration in resolution, as MPH provided more angular sampling compared to conventional LEHR and single pinhole collimator. Funk et al (64) proved that MPH collimators with nine pinholes reduced the axial artifacts and distortion compared to single pinhole for the same number of angular views.…”
Section: Pinhole Pattern and Samplingmentioning
confidence: 99%
“…In this context, the use of multi-pinhole collimation (MPC) has proven to be successful in significantly enhancing the clinical imaging of the brain, thyroid or heart (Beekman & van der Have 2007, Van Audenhaege et al 2015. MPC offers an excellent sensitivity to spatial resolution trade-off for brain imaging (Chen et al 2019), while reducing the fraction of down-scatter counts (Könik, Auer, De Beenhouwer, Kalluri, Zeraatkar, Furenlid & King 2019). Moreover, MPC provides improved penetration characteristics which makes its use more suited for high-energy photon-emitting isotope imaging (e.g., 111 In, 123 I) (Van Audenhaege et al 2013, Könik, Auer, De Beenhouwer, Kalluri, Zeraatkar, Furenlid & King 2019).…”
Section: Introductionmentioning
confidence: 99%